Current Concept Review: Medial Patellofemoral Ligament Reconstruction: From Rehabilitation to Return to Sport - Chao-Jung Hsu; Charlie Lee; Rachel S Christensen; Timothy Y Liu (International Journal of Sports Physical Therapy, 2025)
Medial patellofemoral ligament (MPFL) reconstruction is a surgical procedure to improve the clinical outcomes for recurrent patellar dislocation. Current literature on MPFL reconstruction lacks the details on rehabilitation protocols and the criteria for clearance to sports participation. Additionally, research on biomechanical deficits after MPFL reconstruction remains limited, and psychological factors influencing return to sport (RTS) are often underemphasized. A comprehensive approach integrating clinical criteria, biomechanical assessments, and psychological considerations may optimize rehabilitation outcomes and RTS success. The purpose of this clinical commentary is to provide a comprehensive review of current literature in MPFL reconstruction rehabilitation and outcomes. This commentary will review published rehabilitation protocols to outline phase-specific guidelines. Current literature related to biomechanical characteristics, patient-reported outcomes, impairment and performance-based outcomes and psychological measures will be summarized. Finally, RTS guidelines with objective criteria will be provided. # Level of Evidence Level 5